Dragon's oath - Cast, P. C. (Cast, P. C. House of Night novella., 2011)
"In early 19th century England, long before he's a professor at the Tulsa House of Night, Bryan Lankford is a troublesome yet talented human teen who thinks he can get away with anything--until his father, a wealthy nobleman, has finally had enough, and banishes him to America. When Bryan is Marked on the docks and given the choice between the London House of Night and the dragon-prowed ship to America, he chooses the Dragon--and a brand new fate."--Amazon.com.